THEORETICAL VIEWS AND THE ESSENCE OF SOCIAL CONFLICTS - Rakhmatov Otabek Odilovich (American Journals Publishing, 2023)
Social conflict is the highest stage of the development of contradictions in relations between people, social groups, and society as a whole, which is characterized by a clash of oppositely directed interests, goals, and positions of the subjects of interaction. Conflicts can be hidden or explicit, but they are always based on the lack of agreement between two or more parties. In the field of scientific knowledge, there is a separate science dedicated to conflicts — conflictology